Bioinspired and biomimetic cancer-cell-derived membrane nanovesicles for preclinical tumor-targeted nanotheranostics - Prasad, Rajendra; Mendes, Bárbara B.; Gorain, Mahadeo; Chandra Kundu, Gopal; Gupta, Narendra; Peng, Berney; Aung Win, Eaint Honey; Qing, He; Conde, João (Cell Press, 2023)
Bioinspired cell-membrane-camouflaged nanohybrids have been proposed to enhance tumor targeting by harnessing their immune escape and self-recognition abilities. In this study, we introduce cancer-cell-derived membrane nanovesicles (CCMVs) integrated with gold nanorods (AuVNRs) in addition to therapeutic and imaging cargos such as doxorubicin and indocyanine green. This approach enhances targeted tumor imaging and enables synergistic chemo-phototherapeutics for solid tumors. CCMVs demonstrate significant tumor penetration and retention, serving as nanotheranostics with accessible surface biomarkers, biomimicking properties, and homologous targeting abilities. By evading uptake by the mononuclear phagocytic system, CCMVs can diffuse into the deep tumor core, leading to precise tumor reduction while preserving the surrounding healthy tissues. Notably, intravenous administration of these theranostic agents ensures biocompatibility, as evidenced by a survival period of approximately two months (up to 63 days) without any observed side effects. Our findings underscore the diagnostic and therapeutic potential of this biomimetic nanotheranostics platform.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: biomembrane-coated nanoparticles; breast cancer; cancer nanotherapy; homologous targeting; nanovesicles; synergistic therapeutics; theranostics